2018
DOI: 10.7762/cnr.2018.7.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mineral Contents of Multi-Vitamin and Minerals Currently Sold in South Korea

Abstract: Dietary supplements are popular worldwide and their use has been increasing. The purpose of this study was to evaluate the mineral contents of multi-vitamins and minerals (MVMs) in most commonly sold among dietary supplements. Ninety popular MVM supplements sold in South Korea were surveyed regarding their characteristics and ingredients including minerals listed on the labels through off-line and on-line search. Daily mineral contents of the MVM supplements were compared with Korean Dietary Reference Intakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Maughan et al showed that from a total of 310 questionnaires athletes, supplements were used by 85% of the respondents (27). There is a great need to educate the public for the adequate selection and use of supplements based on the contents and individualís mineral intake derived from the diet (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maughan et al showed that from a total of 310 questionnaires athletes, supplements were used by 85% of the respondents (27). There is a great need to educate the public for the adequate selection and use of supplements based on the contents and individualís mineral intake derived from the diet (30).…”
Section: Resultsmentioning
confidence: 99%
“…Some samples had levels of metals above their maximum allowable levels, but were below permitted daily exposure limit and recommended daily allowance except for Fe in 6% of the samples (32). Comparison of daily mineral dose of zinc, copper, selenium, and chromium in multivitamins and minerals showed a higher level than their RI or AI levels (30). In 2011, 73% of supplement manufacturers inspected by the FDA failed to adhere to 1 or more regulations (33).…”
Section: Resultsmentioning
confidence: 99%